PENGARUH PENGAWET BENZOAT TERHADAP KERUSAKAN GINJAL - Nuwairy Hilda (Universitas Negeri Medan, 2015)
ABSTRACT Benzoate is one type of organic preservatives which is widely used in the food or drink for more than 80 years to suppress the growth of microorganisms. Standard consume benzoate preservative according to BPOM No. 36 in 2013 is 0-5 mg / kg body weight. Excessive use of benzoic acid in the body cause negative impacts that can cause diseases such as lupus, edema, cancer, allergies and damage DNA. The use of benzoic acid in food products is often used among other things in the soft drinks, sauces, soy sauce, dill pickle bottles, butter, margarine, jelly. Benzoate is basically the chemical compounds that are foreign substances that enter with consumed food. If the use of this type and dose is not regulated it causes damages to the user which is toxicity or accumulation of benzoic acid in human organs, especially the kidneys. Kidneys are excretory organs that serve to filter impurities from the blood and throw it together with water in the form of urine. Kata Kunci : Benzoat, ginjal, makanan